2023
DOI: 10.33899/ijvs.2022.133255.2195
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of some equine viral diseases

Abstract: Although different equine viruses' outbreaks have been recorded. However, the most important ones in are the African horse sickness virus (AHSV), equine influenza virus (EIV), equine viral arteritis (EVA), Equine infectious anaemia virus (EIAV), and equine herpes viruses (EHV). To combat these diseases, it is imperative to understand their epidemiological aspects. So, the current review aims to highlight some epidemiological aspects including; causative agents, clinical forms, history, prevalence and geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…There is a shortage of data about mule's natural infection and their epidemiological importance in the transmission. Some studies showed no difference between disease prevalence in the 2 host species (39,59,60).…”
Section: Factors Related To the Host: Latency And Carrier Statusmentioning
confidence: 99%
“…There is a shortage of data about mule's natural infection and their epidemiological importance in the transmission. Some studies showed no difference between disease prevalence in the 2 host species (39,59,60).…”
Section: Factors Related To the Host: Latency And Carrier Statusmentioning
confidence: 99%
“…Prevention of infection of the disease is the first step in the disease control. Early detection of infection through strict active animal inspection and advised sentinel herd monitoring [5]. Once infected animals are situated, prevention of the further spread can achieved by mosquito control and animal movement control.…”
Section: Introductionmentioning
confidence: 99%